Quality of life of dengue patients - Lum, L.C.S.; Suaya, J.A.; Tan, L.H.; Sah, B.K.; Shepard, D.S. (2008)
Although the disease burden of dengue is increasing, the impact on the quality of life (QoL) has not been investigated. A study to determine the QoL of confirmed dengue patients using the EuroQol visual thermometer scale was carried out at the University Malaya Medical Center. Of the 207 participants, 40% were ambulatory and 60% were hospitalized. Of eight health domains, 6.2 and 5.0 domains were affected in the hospitalized and ambulatory cohorts, respectively (P < 0.001), with cognition and interpersonal activities affected most. All patients experienced a drastic decrease in their QoL from the onset of symptoms. The QoL deteriorated to the lowest point (40% of healthy status) between the third and seventh days of illness. The duration of impaired QoL (9 days for ambulatory or 13 days for hospitalized patients) was longer than the duration of fever (5 and 7 days, respectively). Symptomatic dengue has major effects on patients' health.